2001
DOI: 10.1034/j.1600-051x.2001.281209.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical comparison of the effectiveness of novel sonic instruments and curettes for periodontal debridement after 2 months

Abstract: This clinical study demonstrated that Periosonic(R) instruments are clinically at least as effective as curettes in PPD reduction when initial PPD is < or =6 mm and show better clinical attachment level improvement with less recession for initial PPD of > or =7 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 18 publications
3
19
0
2
Order By: Relevance
“…A recent review on the effectiveness of subgingival debridement in general reported PPD reductions of 1.5–2.3 mm in deep periodontal pockets (Van der Weijden & Timmerman 2002). In agreement with previous studies (Beuchat et al 2001, Kocher et al 2001b, Wennström et al 2005), in the present study deeper sites showed the greatest PPD reduction and the greatest gain in CAL.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…A recent review on the effectiveness of subgingival debridement in general reported PPD reductions of 1.5–2.3 mm in deep periodontal pockets (Van der Weijden & Timmerman 2002). In agreement with previous studies (Beuchat et al 2001, Kocher et al 2001b, Wennström et al 2005), in the present study deeper sites showed the greatest PPD reduction and the greatest gain in CAL.…”
Section: Discussionsupporting
confidence: 94%
“…These results are in accordance with data reported in different recent meta‐analyses (Tunkel et al 2002, Van der Weijden & Timmerman 2002, Hallmon & Rees 2003). Beuchat et al (2001) showed a greater PPD reduction in deep periodontal pockets with another sonic scaler (Periosonic: 2.4 mm versus S/RP: 3.0 mm). Loos et al (1989) found a PPD reduction of 2.3 mm in their study.…”
Section: Discussionmentioning
confidence: 88%
“… Beuchat et al (2001)– Periosonic Sculean et al (2004)– Vector Christgau et al (2007)– Vector Kahl et al (2007a, b)– Vector …”
Section: Resultsmentioning
confidence: 99%
“…There are ultrasonic devices which resemble endodontic files such as those used in Endosonics. The first of these was the Periosonic ® (Micro‐Mega, Prodonta SA, Geneva, Switzerland) which was driven by compressed air (Rees et al 1999, Beuchat et al 2001) in a similar manner to a sonic scaler. This instrument was a direct copy from endodontic instrumentation and the idea was to reproduce the flushing and cleansing action of endosonic instrumentation in the root canal but within the periodontal pocket.…”
Section: Review Of Available Instrumentationmentioning
confidence: 99%
“…Systematic reviews have indicated that powered instruments, such as magnetostrictive and piezoelectric ultrasonic scalers and sonic scalers, are at least as effective as curettes in mechanical debridement, but the powered instruments tend to be more efficient (402, 414). There is some evidence that powered instruments may be more effective in areas that are difficult to access, such as furcations and deeper pockets (50, 256). When used properly, the powered instruments appear to remove less root structure (346).…”
Section: Treatment Modalities For Gingivitis and Periodontitismentioning
confidence: 99%